CORONAVIRUS PANDEMIC AND PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES IN CALABAR METROPOLIS - INNOCENT OBETEN OKOI; CHARLES EFFIONG; COMFORT INNOCENT OKOI; EFFIONG ASUQUO OKON (International Studies Journal)
This study was embarked upon to empirically evaluate the impact of Coronavirus pandemic on performance of Small and Medium Enterprises (SMEs) in Calabar Metropolis. Survey research design was used to gather information for the study. The study also used secondary sources of information. This paper is different from other scholars work by delving into COVID 19 pandemic and SMEs performance unlike others that concentrated only on COVID 19 pandemic and its effect on education.  The study has also contributed to literature by exploring other countries affected by COVID 19 pandemic in education, health and agricultural activities. Ordinary least square multiple regression technique was used to analyze the data. From the study, it was revealed that there was a significant impact between lockdown and performance of SMEs in Calabar metropolis. There was significant relationship between restrictions on movement and performance of SMEs within Calabar metropolis. Furthermore, the findings revealed that there was a significant relationship between market closure and performance of SMEs. Finally, there was significant relationship between social distancing and performance of SMEs within Calabar Metropolis. Based on the findings, it was recommended among others that government should revive the economy by providing palliatives (in form of cash) and other incentives   that will cushion the effect of Covid-19 on production and performance of SMEs in Calabar Metropolis.